2010
DOI: 10.1029/2009jd013547
|View full text |Cite
|
Sign up to set email alerts
|

Separating real and apparent effects of cloud, humidity, and dynamics on aerosol optical thickness near cloud edges

Abstract: [1] Aerosol optical thickness (AOT) is one of aerosol parameters that can be measured on a routine basis with reasonable accuracy from Sun-photometric observations at the surface. However, AOT-derived near clouds is fraught with various real effects and artifacts, posing a big challenge for studying aerosol and cloud interactions. Recently, several studies have reported correlations between AOT and cloud cover, pointing to potential cloud contamination and the aerosol humidification effect; however, not many q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 49 publications
2
58
0
Order By: Relevance
“…But this additional correction could be very useful in different applications. It is also possible to verify the current aerosol data sets using the cloud data from the automatic total sky imagers, which have been already in operation at several sites (O'Neill et al, 2003;Jeong and Li, 2010) or using the collocated lidar measurements (Chew et al, 2011;Huang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But this additional correction could be very useful in different applications. It is also possible to verify the current aerosol data sets using the cloud data from the automatic total sky imagers, which have been already in operation at several sites (O'Neill et al, 2003;Jeong and Li, 2010) or using the collocated lidar measurements (Chew et al, 2011;Huang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies indicated that clouds can have a real impact on AOT. These mechanisms of aerosolcloud interaction include aerosol hygroscopic growth, increasing aerosol concentration due to air convergence, and new particles formation in the presence of clouds (Su et al, 2008;Jeong and Li, 2010;Eck et al, 2012Eck et al, , 2014. In addition to the well-known process of hygroscopic particle growth, there is a mechanism of the gas-to-particle conversion that occurs more intensively in the aqueous phase in cloud droplets due to the oxidation of gases (SO 2 , NO x , SOA) (Eck et al, 2014).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Both Jeong and Li (2010) and Eck et al (2014) have noted that the presence of nearby clouds may influence AOD values. They investigated the effect of high RH halos embedded in aerosol layers that typically exist in the vicinity of non-precipitating cumulus clouds.…”
Section: In Situ Uncertaintiesmentioning
confidence: 99%
“…Given the statistical nature of some historical AERONETin situ comparisons as well as the typical model-AERONET comparison constraints, in this section we compare monthly statistics for in situ measurements, AERONET retrievals and AeroCom model output. It should be reiterated here that we are comparing asynchronous data and that there are some additional differences amongst the data sets that need to be kept in mind: the AERONET data are rigorously cloud-screened (although cloud halo effects may persist; e.g., Jeong and Li, 2010) and only obtained during daytime; the in situ measurements are also daytime-only and the airplane did not fly in clouds due to FAA flight restrictions but may have flown near clouds; and the model data include day and night with clouds and also represent values over a 1 × 1 • grid. Figure 8 shows the 440 nm monthly medians of AOD, AAOD and SSA at BND and SGP based on the in situ profile measurements and two versions of AERONET retrievals as described below.…”
Section: Bnd and Sgp: In Situ Vs Aeronet And Aerocom Model Output -Smentioning
confidence: 99%
“…The spectral deconvolution method (O'Neill et al, 2003), which separates fine and coarse mode AOD, further isolates potential cloud effects. Zhang et al (2005) and Jeong and Li (2010) examined satellite and sun photometer derived AODs for marine and continental clouds, respectively. The findings of Zhang et al (2005) suggest that 70 % of the increased satellite signal in AOD in the vicinity of clouds is due to cloud contamination, with the remaining 30 % due to hygroscopicity or secondary production.…”
Section: T F Eck Et Al: Rapid Aerosol Optical Depth Enhancements Nmentioning
confidence: 99%